Financial development and the cost of equity capital: Evidence from China - Jeong-Bon Kim; Mary L. Z. Ma; Haiping Wang (China Journal of Accounting Research, 2015)
This study examines the relation between province-level financial development and the cost of equity in China. Our main findings are that (1) stock market development reduces the cost of equity in general, but the effect diminishes significantly in state-owned enterprises (SOEs) and firms with high growth potential or innovation intensity and (2) banking development only marginally lowers the cost of equity, but the effect is stronger in non-SOEs. Further analysis reveals that stock market development substitutes for such institutional factors as accounting quality, law enforcement, stock market integration and the split-share structure reform in lowering the cost of equity. We also find that lack of banking competition and banking marketization and under-development of the non-state economy partially account for the weak effect of banking development on the cost of equity.
Keywords: G3; G15; G18; 650; Financial development; Cost of equity capital; Law and finance; China